Long-term treatment with leuprorelin for spinal and bulbar muscular atrophy: natural history-controlled study. Issue 12 (5th August 2017) - Hashizume, Atsushi; Katsuno, Masahisa; Suzuki, Keisuke; Hirakawa, Akihiro; Hijikata, Yasuhiro; Yamada, Shinichiro; Inagaki, Tomonori; Banno, Haruhiko; Sobue, Gen
Abstract : Objective: To evaluate the prognosis and progression of spinal and bulbar muscular atrophy (SBMA), a rare X-linked motor neuron disorder caused by trinucleotide repeat expansion in the AR (androgen receptor) gene, after long-term androgen suppression with leuprorelin acetate treatment. Methods: In the present natural history-controlled study, 36 patients with SBMA treated with leuprorelin acetate for up to 84 months (leuprorelin acetate-treated group; LT group) and 29 patients with SBMA with no specific treatment (non-treated group; NT group) were analysed. Disease progression was evaluated by longitudinal quantitative assessment of motor functioning using the revised Amyotrophic Lateral Sclerosis Functional Rating Scale (ALSFRS-R), and the modified Norris score. In addition, we selected two major clinical endpoint events, namely the occurrence of pneumonia requiring hospitalisation and death, to evaluate disease prognosis following long-term leuprorelin acetate treatment. Results: In our analysis of the longitudinal disease progression using the random slope model, we observed a significant difference in the ALSFRS-R total score, the Limb Norris Score, and the Norris Bulbar Score (p=0.005, 0.026 and 0.020, respectively), with the LT group exhibiting a slower per-12-months decline compared with the NT group. As for the event analysis, the prognosis of the LT group was better in comparison to the NT group as for the event-free survival period (p=0.021). Conclusion: Long-term treatment with leuprorelin acetate appears to delay the functional decline and suppress the incidence of pneumonia and death in subjects with SBMA.